Don’t Speak, Maharani: Raising Awareness Towards How Victim Blaming is Worsening Rape Survivor’s PTSD - Arliga Kanza Al-Ayubi (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
The screenplay Don’t Speak, Maharani is the story of Maharani as a rape survivor who suffers from post traumatic stress disorder. Using drama as the genre of the story, the screenplay shows multiple struggles of Maharani who lives her life with unsupportive family which is worsening her psychological state. Since the screenplay focuses on the act of victim blaming which is worsening rape survivor’s Post Traumatic Stress Disorder (PTSD), the story focuses on Maharani reaction towards the action given to her. As the plot advances, it shows how Maharani’s PTSD is worsened by victim blaming given to her. In the end, Maharani tries to heal by taking drugs but she gets overdose. In order to create this screenplay, I use two concepts which are rape and PTSD and rape and victim blaming. The issues regarding victim blaming and PTSD are rarely brought up in a form of a screenplay. However, I believe victim blaming is an act of killing and needs to be stoped. Keyword: Rape, Post Traumatic Stress Disorder, Victim Blaming.